2007
DOI: 10.5194/aab-50-476-2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Birth Weight and Sex on Pre-Weaning Growth Rate of Piglets

Abstract: A study was conducted to find out the effect of birth weight and sex on growth rate of piglets in pre-weaning period. A total of 466 piglets from 48 litters of multiparous sows (Landrace) were involved in the experiment. Using a clustering approach piglets were assigned into three birth weight groups (Heavy (H), Intermediate (I), Light (L)). For the analysis of growth performance, pigs were weighed every 7 days until weaning at 28 days of age and average daily gain (ADG) was calculated. During lactation, body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
2
14
0
1
Order By: Relevance
“…Birth weight in pigs has been linked to differences in both growth rate and body composition. Low birth weight pigs exhibit a 15 % to 30 % lower growth rate (compared to medium and high birth weight pigs) in the 1st month of postnatal life (Campbell & Dunkin 1982, Wolter et al 2002, Poore & Fowden 2004, Gondret et al 2005, Škorjanc et al 2007. Based on chemical analysis of the whole body at birth, Rehfeldt & Kuhn (2006) reported that low birth weight pigs have less fat and protein and more water than their littermates.…”
Section: Resultsmentioning
confidence: 99%
“…Birth weight in pigs has been linked to differences in both growth rate and body composition. Low birth weight pigs exhibit a 15 % to 30 % lower growth rate (compared to medium and high birth weight pigs) in the 1st month of postnatal life (Campbell & Dunkin 1982, Wolter et al 2002, Poore & Fowden 2004, Gondret et al 2005, Škorjanc et al 2007. Based on chemical analysis of the whole body at birth, Rehfeldt & Kuhn (2006) reported that low birth weight pigs have less fat and protein and more water than their littermates.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the BW of piglets was 1.52±0.11 kg, which is higher than the 1.18±0.12 kg of the previous study. It has been reported that birth weight affects weight, growth performance, backfat, and longissimus muscle area from pre-weaning to slaughter (Skorjanc et al, 2007;Fix et al, 2010). Skorjanc et al (2007) reported that high-birth-weight piglets had higher BW at weaning and low-birth-weight piglets had 17 to 22% lower ADG when compared with heavy and intermediatebirth-weight piglets.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was found between the amount of milk produced by a sow and the amount of creep feed consumed by her litter, with the piglets of those sows producing the most milk consuming the most creep feed (Allen and Lasley, 1960;Renaudeau and Noblet, 2001). Skorjanc et al (2007) indicated that neither milk production after the second week of lactation nor consumption of creep feed is sufficient enough to cover the nutrition needs of fast-growing piglets. There is still a lack of optimization of nutrient in the pre-weaning period, especially for heavier piglets with their higher growth potential.…”
Section: Introductionmentioning
confidence: 93%